Set of actions, factions, and jurisdictional conflicts in the final stage of the conquest of Tucumán (XVI century) - Ferreiro, Juan Pablo (AWARI, 2024)
This article puts forth a proposition based on hitherto unpublished information from a file discovered in the This article proposes a linkage between an unpublished source from the Archivo General de Indias and another source from the same archive, edited by R. Levillier more than a century ago. The linkage is based on the premise that the two sources are identical but not in content. The article then presents an annotated and contextualized analytical identification of the linkage plot arising from the testimonies in the two sources. This exploratory and experimental exercise aims to identify and define discrete power networks and their historical consequences. I do not intend to present definitive conclusions at this stage, given that the research is still in progress. Instead, I am exploring a methodological approach that has emerged in South American anthropological and historical disciplines. This involves investigating a relational field in which data is scattered and articulating it with socio-historical processes that are contemporary to them. In this process, I am employing categories of social network analysis, including quasi-group, action set, and faction, to recognize and study such processes.